Optimalisasi Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Tahanan Pada Rumah Tahanan Kelas II B Gianyar - Gumay, Feby Kurnia Rapanca; Dilla, Dian Marva; Olivia, Naila Radha; Prasasti, Ni Made Jyotiara Nandita; Equatora, Muhammad Ali (Indonesian Journal of Community Services, 2023)
Clean and healthy living behaviors, basically changing the environment to be healthier, reducing the spread of disease, people can take advantage of the services and health facilities that have been provided, exercise consistently can make the body fresher and fitter and also protected from various disease viruses, add soul always to be productive, live more neatly organized and always positive thinking. The health of the assisted residents is one of the essential things to be more concerned about regarding PHBS contained in the detention center environment. The Method of Implementing Community Service begins with carrying out observations, preparing programs, and implementing the PHBS program. Optimization of the Implementation of Clean and Healthy Living Behavior (PHBS) Prisoners at the Gianyar Class IIB Detention Center is a form of our implementation and dedication to PKM activities.